Sediment Transport In Sungai Kulim, Kedah - Chang, Chun Kiat (2006)
Effect of rapid urbanization has accelerated the impact on the catchment hydrology and geomorphology. Such rapid development which takes place in river catchment areas will result in higher sediment yield and it will not only affects river morphology, but also river channel stability, causing serious damages to hydraulic structures along the river and also becoming the main cause for serious flooding in urban areas. Therefore, it is necessary to predict and evaluate the river channel stability due to the existing and future developments. This study was carried out at Sungai Kulim in Kedah state, Malaysia, by means of evaluation on sediment transport using recently observed data up to year 2006. The present study attempts to give an overview of the channel changes and sediment transport phenomena in Sungai Kulim. A total of 24 samples of bed materials were collected from four locations (CH 20000, eH 14390, eH 3014 and eH O), and 14 river hydraulics and sediment transport data sets including discharge, bed load, suspended load and total load were collected from two locations (eH 14390 and eH 3014) from 2004 to 2006. The data were used to analyze and evaluate existing Manning equations and sediment transport equations. Attempts were also made to derive new Manning equations (Equations 4.3 and 4.4) with a correlation coefficient, R2 = 0.86 for application to the moderate-size channels in Malaysia. The results of evaluation for total load equations at the two locations along Sungai Kulim show that Engelund & Hansen equation gave the best prediction for sand bed stream and yielded highest percentage of data with discrepancy ratio in between 0.5 and 2.0 (33.33% at CH 14390 and 62.50% at eH 3014). An erodible-boundary model, FLUVIAL-12 which simulates inter-related changes in channel-bed profile, width variation and changes in bed topography was selected for this study. EngelundHansen equation and roughness coefficient, n = 0.030 were selected for the model which was calibrated and validated for water surface profile and bed elevation.